Predictors of childbirth services in Indonesia - Nuzulul Kusuma Putri; Agung Dwi Laksono (Intelektual Pustaka Media Utama, 2022)
The Government of Indonesian implemented maternal health service programs to minimize at-home childbirth services and increase mothers' utilization of its services. There is not enough evidence these policies are effectively decreasing the maternal mortality rate. Hence, this study aimed to analyze the predictors of each specific childbirth services in Indonesia. This study used the secondary dataset of the 2012 Indonesian demographic data survey (IDHS). The sample was 17,769 women ages 15 to 49 years old. We performed logistic regression for the multivariate case to identify the predictors of childbirth service. Geographical, education, and economic condition significantly predict childbirth services. Women who are not residents tend to use a community-based facility than institutionalized health. Women with higher parity, inadequate knowledge on pregnancy danger signs, lower antenatal care visits, and never had any discussion with their husbands about the planned place of giving birth tend to prefer giving birth at home than health facilities. Women's decision to use a safe childbirth service is hindered by demanding access to reach institutionalized healthcare. Our findings highlighted the importance of women empowerment to enable women to utilize safe labor in a health facility.